Building Health Care System Capacity to Respond to Disasters: Successes and Challenges of Disaster Preparedness Health Care Coalitions. Issue 2 (6th February 2015) - Walsh, Lauren; Craddock, Hillary; Gulley, Kelly; Strauss-Riggs, Kandra; Schor, Kenneth W.
Abstract: Introduction: This research aimed to learn from the experiences of leaders of well-developed, disaster preparedness-focused health care coalitions (HCCs), both the challenges and the successes, for the purposes of identifying common areas for improvement and sharing "promising practices." Hypothesis/Problem: Little data have been collected regarding the successes and challenges of disaster preparedness-focused HCCs in augmenting health care system preparedness for disasters. Methods: Semi-structured interviews were conducted with a sample of nine HCC leaders. Transcripts were analyzed qualitatively. Results: The commonly noted benefits of HCCs were: community-wide and regional partnership building, providing an impartial forum for capacity building, sharing of education and training opportunities, staff- and resource-sharing, incentivizing the participation of clinical partners in preparedness activities, better communication with the public, and the ability to surge. Frequently noted challenges included: stakeholder engagement, staffing, funding, rural needs, cross-border partnerships, education and training, and grant requirements. Promising practices addressed: stakeholder engagement, communicating value and purpose, simplifying processes, formalizing connections, and incentivizing participation. Conclusions: Strengthening HCCs and their underlying systems could lead to improved national resilience to disasters. However, despite many successes, coalition leaders are faced with obstacles that may preclude optimal system functioning. Additional research could: provide further insight regarding the benefit of HCCs to local communities, uncover obstacles that prohibit local disaster-response capacity building, and identify opportunities for an improved system capacity to respond to, and recover from, disasters. L Walsh, H Craddock, K Gulley, K Strauss-Riggs, KW Schor .Building health care system capacity to respond to disasters: successes and challenges of disaster preparedness health care coalitions .Prehosp Disaster Med .2015 ;30 (2 ):1 -10 .